Optimalisasi Kelancaran Asi Melalui Kombinasi Ekstrak Daun Katuk Dan Fenugreek Pada Ibu Menyusui Di TPMB Sudarmi S.ST Di Tajinan - Windha Rahma Anggita; Reny Retnaningsih (Journal of Innovative and Creativity, 2025)
For infants under six months of age, breast milk is the finest nourishment. Exclusive breastfeeding is the practice of giving infants only breast milk during the first six months of their life. The prevalence of exclusive breastfeeding varies between 30 and 50 percent worldwide. In 2020, 66.1% of Indonesians were exclusively breastfeeding. The national goal of 80% has not yet been met, however this number has surpassed the 2020 strategic plan objective of 40%. In 2023, Ridha Setiadewi performed a research in Riau and found that one of the primary reasons moms discontinued nursing their newborns and did not offer exclusive breastfeeding was breastfeeding problems. This research is to ascertain how fenugreek and katuk leaf extract might maximize breastfeeding effectiveness in nursing moms at TPMB Sudarmi S.ST in Tajinan. Thirty participants were split into two groups for the study, which used a non-equivalent control group design and a quantitative, quasi-experimental design. One group received a combination of fenugreek and katuk leaf extract, while the other group received no intervention. Data measurement will be carried out with a posttest questionnaire that will be given to all respondents. The research data will be analyzed using bivarat analysis and paired sample t-test statistical test will be used with the significance level set at α = 0.05. The results of the research data analysis showed a probability value of 0.004 < α = 0.05, so H0 was rejected and Ha was accepted. In conclusion, the combination of Sauropus androgynus leaf extract and fenugreek can help optimize the fluency of breast milk in breastfeeding mothers at TPMB Sudarmi, S.ST in Tajinan. It is recommended that health education about the benefits of herbal plants around us be improved. By increasing knowledge of herbal medicine, optimization of breast milk fluency can be improved to increase the rate of exclusive breastfeeding in infants.